Μουσική και μάρκετινγκ: ανάλυση του μουσικού περιεχομένου ελληνικών τηλεοπτικών διαφημίσεων - Θεοφανίδης, Φαίδων Σ. (SPOUDAI Journal of Economics and Business, 2007)
Music although it is frequently used in TV advertising, it has gained, comparatively to other advertising cues such as humor, celebrities, comics etc., little empirical research attention especially in the Greek creative advertising environment. The current paper provides: a) a theoretical review and synthesis of published studies regarding the roles and uses of music, and b) empirical evidence about the degree and the way music is used in Greek TV advertising. More specific, 409 TV commercials were content analysed in relation to 10 music variables. Univariate descriptive data analysis is illustrated for each music variable. The results have important implications for practitioners understanding and using music in TV advertising